Foreign Aid : Challenges and Opportunities - Wolfowitz, Paul (2016)
Paul Wolfowitz, President of the World Bank, discussed Africa’s challenge to unleash the energy of the people, and give people the opportunity to improve their lives themselves. He talked about the challenge of corruption. He appreciated Africa for improving policies to make it easier for new businesses to take off and for businesses that are established to expand. Africans are taking a lead in helping their continent turn the corner, and donors are raising the bar for development assistance to try to ensure that every dollar is used to create a healthier, better-educated, more prosperous Africa. Governance is taken seriously, with performance-based aid strengthening anti-corruption efforts.